Cash Holding pada Perusahaan Non-Keuangan di Indonesia - Juliani, Meily; Tu, Angelline (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
The aim of this study is to empirically prove the effect of accrual quality, earnings quality, company size, market to book ratio operating cash flow, debt financing, capital expenditure, net working capital on cash holdings. The research population is non-financial companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Hypothesis testing was carried out using panel regression analysis. The sampling method used in this study was purposive sampling with a total sample of 415 non-financial companies. The results of the study of firm size have a negative effect on cash holdings. market to book ratio, debt financing, net working capital, and operating cash flow have a positive relationship to cash holdings, while accrual quality, earnings quality, and capital expenditure have insignificant results. Keywords: Cash Holding; Firm Size; Earning Quality